2011
DOI: 10.1242/dev.066241
|View full text |Cite
|
Sign up to set email alerts
|

Barx2 and Fgf10 regulate ocular glands branching morphogenesis by controlling extracellular matrix remodeling

Abstract: SUMMARYThe lacrimal gland (LG) develops through branching morphogenesis and produces secretions, including tears, that lubricate and protect the ocular surface. Despite the prevalence of LG disorders such as dry eye, relatively little is known about the regulation of LG development. In this study, we show that the homeobox transcription factor Barx2 is highly expressed in conjunctival epithelium, eyelids and ocular [lacrimal, harderian (HG), and meibomian (MG)] glands and is necessary for normal ocular gland a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 55 publications
0
57
0
Order By: Relevance
“…Sox9 could also be detected in the retina, retinal pigmented epithelium and the choroid. The murine lacrimal gland begins to form at E13.5 as a projection from the temporal conjunctival epithelium into the surrounding mesenchyme, and the harderian glands originate by a similar process from the nasal part of the conjunctival epithelium at E15.5 (Tsau et al, 2011). At E14.5, Sox9 was expressed in the nuclei of conjunctival and primary lacrimal bud epithelial cells (Fig.…”
Section: Sox9 Is Expressed In the Developing Ocular Glandsmentioning
confidence: 98%
See 2 more Smart Citations
“…Sox9 could also be detected in the retina, retinal pigmented epithelium and the choroid. The murine lacrimal gland begins to form at E13.5 as a projection from the temporal conjunctival epithelium into the surrounding mesenchyme, and the harderian glands originate by a similar process from the nasal part of the conjunctival epithelium at E15.5 (Tsau et al, 2011). At E14.5, Sox9 was expressed in the nuclei of conjunctival and primary lacrimal bud epithelial cells (Fig.…”
Section: Sox9 Is Expressed In the Developing Ocular Glandsmentioning
confidence: 98%
“…Lacrimal and harderian gland development begins on embryonic day (E) 13.5 and 15.5, respectively, when Fgf10 in the periocular mesenchyme interacts with fibroblast growth factor receptor 2b (Fgfr2b) in the ectoderm to induce bud outgrowth Makarenkova et al, 2000;Tsau et al, 2011;Qu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meibomian glands originate from the fused eyelid margin at the late fetal stage (12). Studies of mutant and transgenic mice have shown that tumor necrosis factor receptor-associated factor 6 (5), C/EBP␣ and -␤ (6), ectodysplasin-A receptor signaling (13), bone morphogenetic protein signaling (14,15), homeodomain transcription factor BARX2 (16), and kruppel-like factor 5 (17) are important for meibomian gland development. In contrast, SCD1 is important for meibum production (3,8).…”
mentioning
confidence: 99%
“…The Mtap1B (52.9 cM) gene regulates microtubular recombination. Furthermore, Mtap1B knockout mice developed blindness due to retinopathy (Meixner et al, 2000;Ma et al, 2003;Tsau et al, 2011). RT-PCR and sequencing analysis were used to confirm mutations in Fgf10 ( Figure 7A and B), Plk2 (data not shown), and Mtap1B ( Figure 7F and G) genes, all of which are involved in eyelid development in B6-Co mice.…”
Section: Mutant Gene Mapping and Candidate Gene Analysismentioning
confidence: 99%